2010
DOI: 10.1136/adc.2010.184291
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late MRI in asphyxiated newborns treated with hypothermia

Abstract: Objective The purposes of this feasibility study are to assess: (1) the potential utility of early brain magnetic resonance imaging (MRI) in asphyxiated newborns treated with hypothermia; (2) whether early MRI predicts later brain injury observed in these newborns after hypothermia is completed; and (3) whether early MRI indicators of brain injury in these newborns represent reversible changes. Patients and Methods All consecutive asphyxiated term newborns meeting the criteria for therapeutic hypothermia wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 30 publications
(53 reference statements)
4
54
1
2
Order By: Relevance
“…Whereas one normothermic newborn had minor focal white matter injury detected on day 10 after normal imaging, there was a delay in the development of BN-predominant injury on day 10 in two hypothermic newborns. The delayed development in the features of acute, profound asphyxia on the 10th day of life in these two hypothermic newborns suggests that the process of injury continues to evolve after cessation of hypothermia at 72 h. In term newborns with HIE not treated with hypothermia, the predominant pattern of brain injury is robustly detected on the third day of life (15), but in those treated with hypothermia, the earliest time at which that predominant pattern is fully established still needs to be determined (16).…”
Section: Evolution Of Mri Dti and Mrsi In Term Hiementioning
confidence: 95%
“…Whereas one normothermic newborn had minor focal white matter injury detected on day 10 after normal imaging, there was a delay in the development of BN-predominant injury on day 10 in two hypothermic newborns. The delayed development in the features of acute, profound asphyxia on the 10th day of life in these two hypothermic newborns suggests that the process of injury continues to evolve after cessation of hypothermia at 72 h. In term newborns with HIE not treated with hypothermia, the predominant pattern of brain injury is robustly detected on the third day of life (15), but in those treated with hypothermia, the earliest time at which that predominant pattern is fully established still needs to be determined (16).…”
Section: Evolution Of Mri Dti and Mrsi In Term Hiementioning
confidence: 95%
“…There were also frequent comparisons of early US to MRI done several days later. The injury typically becomes more apparent with time, partially explaining why MRI appears to be more diagnostic than US [66,67]. High-end US done concurrently with MRI has 95% diagnostic accuracy compared to MRI [68].…”
Section: Reliability and Predictive Value Of Us Findingsmentioning
confidence: 99%
“…Recent studies demonstrated that early MRI (performed in the first week of life) could reliably predict the extent and severity of brain injury observed on later MRI (performed after day 7, considering the first day of life as day 1) in asphyxiated neonates treated with hypothermia [7][8][9][10][11]. Nevertheless, to our knowledge, the prognostic value of early and late MRI had not been compared in these neonates.…”
Section: Introductionmentioning
confidence: 97%